Clinical Establishments Act to Check Quality of Health-care Delivery System in India (Indian Internet Journal of Forensic Medicine and Toxicology, 2017)
Introduction: Quality of care provided by the health-care delivery system has come into sharp focus in most of the countries including India. As the quality in health-care delivery system is a crucial factor, so, initiatives to address quality healthcare have become an issue. Methods: The Clinical Establishment Act was reviewed and analysed. Discussion: According to planning commission, human resource and health, India has 250 health workers per lakh population. The target of WHO is 500 per lakh population. There is a huge demand of medical professional against its production. Under these circumstances, however justified, to check the quality health-care services throughout the country is a huge task. Moreover, current pattern of the health-care delivery system does not provide enough incentives for improvement in efficiency. The mechanisms used to produce greater efficiency, accountability, transparency and more responsible administration in hospitals are yet to be deployed in India. Conclusion: Under the present circumstances, there is a need to establish regulatory bodies and systems to monitor clinical and non-clinical establishment and the services offered in the public and private facilities.
Keywords: Health-care system; India; Legal obligations; Check quality; Registration of clinics; Uniform standard